Assessing semi-outdoor thermal environment at higher learning institution in a hot humid climate / Nurul Atiqah Azmi, Fairus Muhamad Darus and Rabiatul Adawiyah Nasir - Azmi, Nurul Atiqah; Muhamad Darus, Fairus; Nasir, Rabiatul Adawiyah (College of Built Environment, 2023)
Outdoor thermal comfort (OTC) refers to a person's subjective perception of the temperature and other thermal conditions in an outdoor environment.